PERBEDAAN PERILAKU SEKS DALAM BERPACARAN PADA REMAJA PRIA DAN WANITA DI SMK SWASTA JAMBI MEDAN TAHUN 2015 - devi pasaribu; Sri Rahayu Sanusi; Asfriyati . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Sex behavior is something related to the genitals or things related to things of the intimate dating between men and women. This research aims to know the difference in dating sex behavior in adolescent men and women in SMK Swasta Jambi Medan in 2015. A kind of this research is a descriptive study by qualitative approach study using case study design by depth interview. The subject is adolescent man and women age 15 - 17 years old that consist of sixteen people in SMK Swasta Jambi Medan in 2015. It was conducted on December 2014 - Agustus 2015. The results of research indicates that the difference in dating sex behavior in adolescent men and women the existence of the base of coercion against adolescent women. The things that cause the adolescent do the sex behavior relation is the influence of pornography movie or video, the influence of peers, boyfriend or girlfriend, and the poor supervision from their parent s and family. And the background of sex behavior in adolescent the existence of a sense of shame, carried away, and the coercion factor. It is suggested to the informant do not have sex at a young age, increase the value of religious. The teacher can be the second parents for adolescent in order to guide the adolescents. As a health team, can do to provide counselling about sex, the reproduction health and its impact to the health. It hope the support of government to prevent behavior sex in adolescent in order to unintended pregnancy. Keywords : Adolescent, Sex Behavior, Dating